Green Economy: Opportunities and Challenges for the Renewable Energy Sector in Indonesia - Dakhi, Hermanfland; Hukom, Alexandra; Perwira Ompusunggu, Dicky (Center for Economics, Business and Entrepreneurship Development Faculty of Economics and Business, Universitas Muhammadiyah Malang, 2025)
This research explores the opportunities and challenges of the renewable energy sector—specifically geothermal, wind, bioenergy, and solar—in supporting the green economy in Indonesia. The study examines Indonesia’s commitment to the Enhanced Nationally Determined Contributions (ENDC) to reduce greenhouse gas emissions by 31.89% through domestic efforts and 43.2% with international assistance by 2030. A normative economic research approach, based on secondary data analysis, is used to evaluate existing energy policies, such as the Domestic Market Obligation (DMO), and their impact on economic growth and the environment. Findings indicate that innovation in the renewable energy sector not only enhances efficiency and productivity but also mitigates environmental harm. However, significant barriers to implementation remain. As domestic energy demand continues to rise due to economic and population growth, sustainable and innovative solutions are essential to ensuring inclusive and environmentally friendly economic development.